The Impact of Internal Audit on the Quality of Insurance Performance: A Study on Some Insurance Companies in Iraq - Khalid Khanjar Manssor AL-Saedi; Sonda Weli (Migration Letters, 2023)
This study examines the extent to which the internal auditing affects the quality of insurance performance (QIP) of the Iraqi companies. It also detects whether the Iraqi companies have a good internal auditing system that keeps pace with global developments in improving their insurance performance. The research adopted the descriptive and analytical approach in identifying and treating its variables, which are internal audit as an independent variable with its dimensions (leadership, strategy, risk assessment), and QIP as a dependent variable. For the purpose of achieving the research objectives, three main hypotheses were formulated, which were tested on 280 financial and quality employees, numbering employees in insurance companies in Iraq. Data were processed using (SPSS V25) to extract the arithmetic mean, standard deviation, relative importance, Cronbach’s alpha coefficient, Pearson correlation coefficient, simple and multiple linear regression coefficient as well as using Microsoft Excel 2010. The study revealed a statistically significant influence correlation between the quantitative and qualitative requirements in internal auditing on the quality of performance insurance in insurance companies in Iraq.